Analysis Of The Effectiveness Of Combination Antihypertension Therapy On Blood Pressure Control - Eka Wisnu Kusuma (International Journal of Health Sciences, 2026)
Background : Hypertension is one of the leading non- communicable diseases contributing to cardiovascular morbidity and mortality worldwide . Despite the availability of various antihypertensive agents , many patients fail to achieve recommended blood pressure targets . Current clinical guidelines recommend combination antihypertensive therapy for patients with stage 2 hypertension or high cardiovascular risk because it provides greater blood pressure reduction than monotherapy . However , real- world evidence regarding the effectiveness of combination therapy remains essential. Objective : To analyze the effectiveness of combination antihypertensive therapy in achieving blood pressure control among hypertensive patients. Methods : A retrospective cohort study was conducted using medical records of hypertensive patients receiving combination antihypertensive therapy between January and December 2025. A total of 150 patients were selected through consecutive sampling. Variables included patient characteristics , antihypertensive combination regimen , comorbidities , treatment duration , and blood pressure control . Data were analyzed using descriptive statistics , Chi- square tests , and multivariate logistics regression. Results : The most frequently prescribed regimen was ACE inhibitor plus calcium channel blocker (40.7%), followed by ARB plus calcium channel blocker (28.0%) and ACE inhibitor plus diuretic (21.3%). Overall , 72.0% of patients achieved target blood pressure . ACE inhibitor plus calcium channel blocker therapy was significantly associated with better blood pressure control (p<0.05). Longer treatment duration and medication adherence were also associated with successful blood pressure control. Conclusion : Combination antihypertensive therapy effectively improves blood pressure control among hypertensive patients . ACE inhibitor plus calcium channel blocker demonstrated superior effectiveness compared with other combination regimens.